Relationship between sport experience and anthropometric indices and sport performance in world women's handball championship'2009 - Kniubaite, A.; Skarbalius, A. (Education. Physical training. Sport, 2012)
Research background and hypothesis. The increasing demand for ever higher top level has meant greater interest and research into the factors which influence performance and sporting achievements. Handball is a complex sport whereby performance can be analyzed and presented in a variety of ways. We hypothesized that teams with players with higher anthropometric indices and greater sporting experience had better possibilities in winning a match-play. Research aim was to assess the interaction between players` height, body mass, body mass index (BMI), age, sports experience and sport performance in the World Women`s Handball Championship`2009 (WWHC`2009). Research methods. The data sets were collected from the IHF website (www.ihf.info). We analyzed the height, body mass, body mass index (BMI), sporting experience (international matches played and goals scored) of 390 players as well as their influence on winning points (Pearson`s correlation) and final ranking position (Spearman`s Correlation) of WWHC`2009. Research results. Champions from Russia, the first four seat players and European women players were greater in body size (height, body mass), and sports experience. Discussion and conclusions. Teams composed of players with greater experience had more possibilities to win (r = 0.719; p < 0.001; Y = 0.1571x + 4.9104; r² = 0.5183), but body mass had negative influence (r = 0.317; Y = 0.5353x - 25.598; r² = 0.1008) as well as BMI (r = -0.3300.; Y = -2.0762x + 57.273; r² = 0.1089). The height of players had moderate influence (r = 0.551; p < 0.001) on wining a match-play. It should be noted that the players in the last elite-level competition (European Women`s Handball Championship`2010) showed the same tendency and were taller and heavier than the players of WWHC`2009.